2010
DOI: 10.1007/s11764-010-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and course of chronic fatigue in long-term breast cancer survivors

Abstract: BackgroundThe course of fatigue in long-term breast cancer survivors (BCSs) is unknown. The current study examined chronic fatigue (CF) cross-sectionally and longitudinally in relapse-free women up to 10 years after multimodal treatment for BC stage II/III. The prevalence of persistent fatigue (PF: having CF at two assessments separated by >2 years) and its predictors were also investigated.MethodsData from questionnaires (including the Fatigue Questionnaire and questions regarding socio-demographics and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
112
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(136 citation statements)
references
References 35 publications
14
112
1
4
Order By: Relevance
“…In comparison, (using the same instrument to measure severe fatigue as in the present study) 12.6% of the general Norwegian female population report severe fatigue (Loge, Ekeberg, & Kaasa, 1998 of breast cancer survivors reported fatigue ≥ 2 years after diagnosis (Reinertsen et al, 2010). Thus, it appears that fatigue may continue for five years or more following treatment.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In comparison, (using the same instrument to measure severe fatigue as in the present study) 12.6% of the general Norwegian female population report severe fatigue (Loge, Ekeberg, & Kaasa, 1998 of breast cancer survivors reported fatigue ≥ 2 years after diagnosis (Reinertsen et al, 2010). Thus, it appears that fatigue may continue for five years or more following treatment.…”
Section: Discussionmentioning
confidence: 50%
“…A substantial proportion of breast cancer survivors experience fatigue (Minton & Stone, 2008;Reinertsen et al, 2010). Fatigue involves subjective sensations of tiredness, weakness, and/or lack of energy (J. E. Bower et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Norwegian studies have shown that 25-35 % of long-term survivors of breast cancer, lymphoma and cervical cancer are affected by chronic fatigue (4,(13)(14)(15), and that 26 % and 13 % of hormone-naïve men reported chronic fatigue two years after radical radiotherapy and radical prostatectomy for prostate cancer, respectively (16). Recently it was demonstrated that the prevalence of chronic fatigue in Norwegian testicular cancer survivors increased from 15 % twelve years after treatment to 27 % seven years later (17).…”
Section: Measurement and Prevalencementioning
confidence: 99%
“…Comorbid conditions or other late effects and symptoms such as cardiovascular disease, pulmonary disease, overweight, sleep disturbance, hormonal changes, peripheral neuropathy, and persistent pain may also be contributory factors (3,13,14,16,17).…”
Section: Associated Factorsmentioning
confidence: 99%